2005
DOI: 10.1097/01.wnr.0000175611.26485.c8
|View full text |Cite
|
Sign up to set email alerts
|

Figure–ground segregation requires two distinct periods of activity in V1: a transcranial magnetic stimulation study

Abstract: Discriminating objects from their surroundings by the visual system is known as figure-ground segregation. This process entails two different subprocesses: boundary detection and subsequent surface segregation or 'filling in'. In this study, we used transcranial magnetic stimulation to test the hypothesis that temporally distinct processes in V1 and related early visual areas such as V2 or V3 are causally related to the process of figure-ground segregation. Our results indicate that correct discrimination betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 24 publications
7
64
2
Order By: Relevance
“…Ventral-temporal activation was extensive in control children, including bilateral parahippocampal regions typically activated during spatial analysis (Epstein & Kanwisher, 1998) and lateral fusiform gyri typically activated during object processing (Grill-Spector, 2003). Furthermore, control children activated primary visual cortices implicated in low-level figure-ground segregation (Heinen et al, 2005;Skiera et al, 2000) bilaterally, consistent with past EFT findings in adult controls (Ring et al, 1999). Reduced involvement of left occipital regions in ASD relative to control children suggests less reliance on lower-level visual processing.…”
supporting
confidence: 75%
“…Ventral-temporal activation was extensive in control children, including bilateral parahippocampal regions typically activated during spatial analysis (Epstein & Kanwisher, 1998) and lateral fusiform gyri typically activated during object processing (Grill-Spector, 2003). Furthermore, control children activated primary visual cortices implicated in low-level figure-ground segregation (Heinen et al, 2005;Skiera et al, 2000) bilaterally, consistent with past EFT findings in adult controls (Ring et al, 1999). Reduced involvement of left occipital regions in ASD relative to control children suggests less reliance on lower-level visual processing.…”
supporting
confidence: 75%
“…In all experiments and analyses, earlier components of the VEP remained unaffected: Latencies of the P100 did not show any relation with RT, thus suggesting that in texture discrimination tasks, visually guided behavior depends on processes taking place approximately 175-275 msec after stimulus presentation. As argued earlier, these processes reflect scene segmentation, a process critically dependent on recurrent interactions between higher and lower visual areas, and possibly related to visual awareness Heinen et al, 2005). As previous work has shown that scene segmentation does not depend on attention, it is unlikely that changes in attentional capture can explain the pattern of results we observed (Scholte, Witteveen, Spekreijse, & Lamme, 2006;Schubö, Meinecke, & Schröger, 2001).…”
Section: Results Experiments 1: Differences In Rt Correspond To Latenccontrasting
confidence: 42%
“…Visual processing of texture checkerboards requires texture segregation, which is a two-stage process: First, borders of figures are detected, and subsequently, the figures are filled in. Border detection occurs around 80-90 msec, and is likely to be the result of lateral inhibition within cortical areas, whereas figure filling-in can take up to 200 msec and depends on re-entrant processing (Scholte, Jolij, Fahrenfort, & Lamme, 2008;Jehee, Roelfsema, Deco, Murre, & Lamme, 2007;Heinen et al, 2005;Roelfsema, Lamme, Spekreijse, & Bosch, 2002;Caputo & Casco, 1999;Lamme, 1995). This latter stage has been linked to perceptual awareness of texture stimuli, whereas the former stage could be sufficient in order to detect presence of a texture stimulus Heinen et al, 2005;Lamme, 1995Lamme, , 2003Supèr, Lamme, & Spekreijse, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological data also provide evidence for cross-talk between visual areas located at different hierarchical level. In fact transcranial magnetic stimulation (TMS) studies (22)(23)(24)(25)(26) reported that single-pulse TMS applied over primary visual areas produces significant perceptual impairment in two distinct time windows: an early one and a late one, relative to the presentation of a visual stimulus. The perception impairment caused by stimulation during the second (late) time window was interpreted as a consequence of an interference with a top-down reactivation of V1 (27,28).…”
mentioning
confidence: 99%